Safer Interactive Medical Device Design: Insights from the CHI+MED Project - Curzon, Paul; Blandford, Ann; Thimbleby, Harold; Cox, Anna (EAI Endorsed Transactions on Security and Safety, 2015)
Interactive medical devices such as infusion pumps, monitors and diagnostic devices help save lives. However, they are also safety critical in that they may fail in use and patient harm or death ensue. It is not just that the software and hardware should meet their specification. The design should help ensure users do not make mistakes. Safety factors become more important as medical devices become mobile and are used by patients as part of their everyday life rather than by trained professionals in well-defined hospital environments. Regulators are increasingly taking home-use seriously as a result of device recalls due to devices that have caused patient harm. We give insights from the research on the CHI+MED project (www.chi-med.ac.uk). It has focussed on understanding how the design of interactive medical devices can support safety. CHI+MED also developed practical tools and guidance that we review.
Keywords: safety; medical devices; interaction design